Resistencia de variedades de abacá (Musa textilis Nee) a la mancha de la hoja y pérdidas ocasionadas por la enfermedad - LOPEZ, R.; Loegering, W.Q. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Brown leaf spot of abaca (Musa textilis Nee) is a widely distributed disease in the abaca plantations of Central America. The symptoms of the disease are similar to the leaf spot of banana caused by Helminthosporium torulosum (Syd.) Ashby and Cordana musae (Zimm.) Hohn. The variety Bunglanon is much more susceptible to the disease than Libuton, Maguindanao, Tangongon, and Putian. It was found that as much as 13.7 per cent of the total leaf area of Bunglanon plants was destroyed by the disease; however, in a study where leaf area of plants was reduced by cutting off the leaves it was found that a reduction of 25 per cent of the leaf area had little or no effect on growth of the plant. A reduction of as much as 62.5 per cent in leaf area did significantly reduce growth in height but the reduction in total growth was small. It is concluded, therefore, that brown leaf spot of abaca is a minor disease. Photostatic copy of the English original may be obtained from the Scientific Communications Service, Inter-American Institute of Agricultural Sciences, Turrialba, Costa Rica.